Epidemiology, outcomes, and risk factors of traumatic brain injury in Bangladesh: a prospective cohort study with a focus on road traffic injury-related vulnerability - Rahman, Farah Naz; Das, Sukriti; Kader, Manzur; Mashreky, Saidur Rahman (Frontiers in Public Health, 2025)
BackgroundLow-and middle-income countries bear a disproportionate burden of traumatic brain injury (TBI), with significant consequences for affected individuals and health systems. However, evidence on the incidence, risk factors, and associated vulnerability—particularly from road traffic injuries (RTIs)—remains limited in South Asia, including Bangladesh, which has one of the highest RTI burdens globally. This study aimed to investigate the epidemiology, clinical characteristics, health outcomes of TBI, and the vulnerability and risk factors associated with RTI-related TBI in Bangladesh.MethodsA prospective observational cohort study was conducted at Dhaka Medical College and Hospital from May to June 2017. Data were collected during patient admission and at 30-day follow-up (or discharge). Registered medical practitioners used a semi-structured questionnaire to collect data, including the Glasgow Coma Scale (GCS), Glasgow Outcome Scale (GOS), and EuroQol-5D-3L. Descriptive analysis was used to present the incidence, clinical characteristics, outcomes, and pre-hospital care scenarios for TBI. The Chi-square test and multivariable logistic regression analysis were performed to identify the vulnerability of RTI-related TBI and its predictive factors for mortality.ResultsThe study followed 659 TBI cases. The mean age was 32.3 years, and the majority (80.1%) were male. RTIs were the leading cause of TBI (62%), followed by physical assault (17%) and falls (16%). The mortality rate was 10.3% (n = 68). Patients with RTI-related TBI had 1.95 times higher odds (95% CI 1.21–3.14) of severe GCS scores (<8) and three times higher odds (95% CI 1.59–5.78) of mortality compared to other causes. Predictive factors for mortality included severe GCS (<8) (aOR 8.1, p < 0.01, 95% CI 4.1–16.2), loss of consciousness >1 h (aOR 4.4, p < 0.01, 95% CI 1.4–8.1), and treatment initiation delay >8 h (aOR 2.8, p < 0.01, 95% CI 1.4–5.5). Nearly all patients lacked first aid and emergency transport, and two-thirds were referred from primary and secondary facilities, with one-third receiving no treatment before referral.ConclusionRTI is the most vulnerables, duration of unconsciousness, and treatment delays are key predictors of mortality. These findings can inform policy for prevention and management of TBI in Bangladesh and similar settings.